BOT SPAMMER DETECTION IN TWITTER USING TWEET SIMILARITY AND TIME INTERVAL ENTROPY - Rizal Setya Perdana; Tri Hadiah Muliawati; Reddy Alexandro (Jurnal Ilmu Komputer dan Informasi, 2015)
The popularity of Twitter has attracted spammers to disseminate large amount of spam messages. Preliminary studies had shown that most spam messages were produced automatically by bot. Therefore bot spammer detection can reduce the number of spam messages in Twitter significantly. However, to the best of our knowledge, few researches have focused in detecting Twitter bot spammer. Thus, this paper proposes a novel approach to differentiate between bot spammer and legitimate user accounts using time interval entropy and tweet similarity. Timestamp collections are utilized to calculate the time interval entropy of each user. Uni-gram matching-based similarity will be used to calculate tweet similarity. Datasets are crawled from Twitter containing both normal and spammer accounts. Experimental results showed that legitimate user may exhibit regular behavior in posting tweet as bot spammer. Several legitimate users are also detected to post similar tweets. Therefore it is less optimal to detect bot spammer using one of those features only. However, combination of both features gives better classification result. Precision, recall, and f-measure of the proposed method reached 85,71%, 94,74% and 90% respectively. It outperforms precision, recall, and f-measure of method which only uses either time interval entropy or tweet similarity.